Indecision Points : George W. Bush and the Israeli-Palestinian Conflict - Zoughbie, Daniel, 1984- (Book collections on Project MUSE., 2014)
"Although George W. Bush memorably declared, 'I'm the decider, ' as president he was remarkably indecisive when it came to U.S. policy toward the Israeli-Palestinian conflict. His administration's policymaking featured an ongoing clash between moderate realists and conservative hard-liners inspired by right-wing religious ideas and a vision of democracy as cure-all. Riven by these competing agendas, the Bush administration vacillated between recognizing the Palestinian right to self-determination and embracing Israeli leaders who often chose war over negotiations"--Front flap.